Spectrum gamma ray borehole logging wire data of MeBo sediment core GeoB16601-7 - Tim Freudenthal (PANGAEA, 2020)
Logging was performed with the sea floor drill rig MARUM-MeBo70 in a borehole drilled with a 103 mm diameter bit. The 1460 Slimhole Memory SGR instrument developed by ANTARES Datasystems GmbH was used. A CsI(Na) crystal with outer diameter of 37 mm and 250 mm length is used as detector. The probe provides Natural Gamma Ray counts and analyses the spectrum for the concentrations of the natural gamma ray emitters potassium, thorium and uranium with an accuracy of about 10%. The probe was deployed in the memory mode with the logging string being inserted into the drill string. The measurement was conducted as upcast by hooking up the probe inside the drill string with a wire. The trip out speed was about 3 cm/s and the logging frequency was 1 Hz. Data processing was conducted using the Antares software GeoBase5 including an environmental correction compensating for the attenuation of the gamma ray signal by the drill pipe.